Seismic Subduction Zone Modeling Based on Earthquake Data in Gorontalo and Surrounding Areas - Moh. Ramdan Lipoeto; Dewa Gede Eka Setiawan; Icha Untari Meidji; Meilan Demulawa; Harsano Jayadi (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2025)
The Gorontalo region is located in an active tectonic zone, so it has a high level of seismic activity. Understanding the geometry of the subduction zone in this region is important for assessing earthquake hazards and disaster mitigation efforts. This study models the angle and depth of subduction of the subduction plate beneath the surface of the Gorontalo region using earthquake data from the USGS catalog from 1994 to 2024. The analysis was carried out using the vertical section method (cross-section), which divides the study area into three segments, namely A, B, and C. Each segment was analyzed using polynomial regression to determine the subduction pattern. The results show that the megathrust zone is at a depth of < 50 km, while the Benioff zone reaches up to 300 km. The obtained subduction angles are 49.01°-59.09° in Segment A, 6.49°-71.76° in Segment B, and 19.87°-58.15° in Segment C. These results show variations in subduction geometry that reflect the tectonic complexity of the Gorontalo region.